Case Study of Somaclonal Variation in Resistance Genes Mlo and Pme3 in Flaxseed (Linum usitatissimum L.) Induced by Nanoparticles - Inese Kokina; Ilona Mickeviča; Marija Jermaļonoka; Linda Bankovska; Vjačeslavs Gerbreders; Andrejs Ogurcovs; Inese Jahundoviča (International Journal of Genomics)
Nanoparticles influence on genome is investigated worldwide. The appearance of somaclonal variation is a cause of great concern for any micropropagation system. Somaclonal variation describes the tissue-culture-induced phenotypic and genotypic variations. This paper shows the results of somaclonal variation in two resistance genes pectin methylesterase and Mlo-like protein in all tissue culture development stages, as donor plant, calluses, and regenerants of Linum usitatissimum induced by gold and silver nanoparticles. In this paper, it was essential to obtain DNA material from all tissue culture development stages from one donor plant to record changes in each nucleotide sequence. Gene region specific primers were developed for resistance genes such as Mlo and Pme3 to define the genetic variability in tissue culture of L. usitatissimum. In recent years, utilization of gold and silver nanoparticles in tissue culture is increased and the mechanisms of changes in genome induced by nanoparticles still remain unclear. Obtained data show the somaclonal variation increase in calluses obtained from one donor plant and grown on medium supplemented by gold nanoparticles (Mlo 14.68±0.98; Pme3 2.07±0.87) or silver nanoparticles (Mlo 12.01±0.43; Pme3 10.04±0.46) and decrease in regenerants. Morphological parameters of calluses showed a number of differences between each investigated culture group.